Phosphate Prodrugs: An Approach to Improve the Bioavailability of Clinically Approved Drugs - Tantra, Tanmoy; Singh, Yogesh; Patekar, Rohan; Kulkarni, Swanand; Kumar, Pradeep; Thareja, Suresh (Current Medicinal Chemistry, 2024)
The phosphate prodrug approach has emerged as a viable option for increasing the bioavailability of a drug candidate with low hydrophilicity and poor cell membrane permeability. When a phosphoric acid moiety is attached to the parent drug, it results in a several-fold elevation in aqueous solubility which helps to achieve desired bioavailability of the pharmaceutically active parental molecule. The neutral phosphate prodrugs have rapid diffusion ability through the plasma membrane as compared to their charged counterpart. The presence of phosphate mono ester breaking alkaline phosphatase (ALP) enzyme throughout the whole human body, is the main consideration behind the development of phosphate prodrug strategy. The popularity of this phosphate prodrug strategy is increasing nowadays due to the fulfillment of different desired pharmacokinetic characteristics required to get pharmaceutical and therapeutic responses without showing any serious adverse drug reactions (ADR). This review article mainly focuses on various phosphate prodrugs synthesized within the last decade to get an improved pharmacological response of the parent moiety along with various preclinical and clinical challenges associated with this approach. Emphasis is also given to the chemical mechanism to release the parent moiety from the prodrug.
Keywords: adverse drug reactions